Community Coalition : how one organization achieves successful leadership succession - Silver, Nora, (SAGE business cases., 2022)
Community Coalition believes its "people first" culture will transform social and economic conditions in South Los Angeles. This nonprofit trains young people to grow into tomorrow's leaders. It was founded by California Congressmember Karen Bass thirty years ago to ensure political power from the ground up thrived in her community. CoCo intentionally created "bench strength," negotiated issues of race and gender, and planned for successful leadership transitions. What key practices enabled effective succession transitions and how can they be replicated in other organizations? While CoCo is a cutting-edge example of successful succession planning, can it excel in finding its fourth CEO?